Caregiving and Caregivers: Concepts, Caregiving Models, and Systems - Charalambous, Andreas (My University, 2023)
The increasing number of care-dependent people leads to a high demand of economic burden for most healthcare systems. This has also led to an increase on the demand for informal care, usually assumed by a family member or a significant other. Informal care is the provision of unpaid care or support to others who need help or who are unable to care for themselves due to long-term health conditions and disability. This chapter provides an overview of the informal caregiving concepts and models, placing also emphasis on the tasks that the role can entail across the disease continuum. The chapter also discusses the scale of informal caregiving around the world including its financial implications for the caregivers themselves. Finally, the chapter takes a look at the challenges that the COVID-19 has placed on informal caregiving.
Keywords: Caregiver; Caregiving; Caregiving models; Informal care